2018
DOI: 10.1038/s41589-018-0144-y
|View full text |Cite
|
Sign up to set email alerts
|

Structure-guided development of YEATS domain inhibitors by targeting π-π-π stacking

Abstract: Chemical probes of epigenetic ‘readers’ of histone posttranslational modifications (PTMs) have become powerful tools for mechanistic and functional studies of their target proteins in normal physiology and disease pathogenesis. Here we report the development of the first class of chemical probes of YEATS domains, newly identified ‘readers’ of histone lysine acetylation (Kac) and crotonylation (Kcr). Guided by the structural analysis of a YEATS-Kcr complex, we developed a series of peptide-based inhibitors of Y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
113
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(116 citation statements)
references
References 58 publications
3
113
0
Order By: Relevance
“…Importantly, targeting this H3K4me3-specific reader could also be beneficial for coinciding blocking of all three oncogenic proteins. Histone readers are increasingly considered to be druggable, and a number of potent inhibitors of acetyllysine recognizing bromodomain and YEATS domain have been developed in the past 10 years [24][25][26][27] . The pioneering studies 8,9,22 uncovering the pivotal role of the histone binding by the PHD finger of KDM5A, PHF23, and BPTF in NUP98 fusions in leukemic transformation and the feasibility of targeting these fusions by small molecules together with our mechanistic findings further suggest that impairing the PHD finger function and/or structure may provide an effective way to treat AMLs associated with these NUP98 fusions.…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, targeting this H3K4me3-specific reader could also be beneficial for coinciding blocking of all three oncogenic proteins. Histone readers are increasingly considered to be druggable, and a number of potent inhibitors of acetyllysine recognizing bromodomain and YEATS domain have been developed in the past 10 years [24][25][26][27] . The pioneering studies 8,9,22 uncovering the pivotal role of the histone binding by the PHD finger of KDM5A, PHF23, and BPTF in NUP98 fusions in leukemic transformation and the feasibility of targeting these fusions by small molecules together with our mechanistic findings further suggest that impairing the PHD finger function and/or structure may provide an effective way to treat AMLs associated with these NUP98 fusions.…”
Section: Resultsmentioning
confidence: 99%
“…This suggests that pharmacological inhibition of the ENL YEATS domain is a potential therapeutic target for AMLs such as MLL -r leukemias (Erb et al, 2017; Wan et al, 2017). Subsequently, another two research groups separately described small molecules capable of inhibiting the YEATS domains of AF9/ENL (Christott et al, 2018; Li et al, 2018). Christott et al (2018) screened a library of 24,000 compounds using a peptide displacement assay and discovered a small molecule (XS018661) that binds to AF9 and ENL with equilibrium dissociation constant ( K d ) values of 523 ± 53 and 745 ± 45 nM, respectively, as determined by isothermal calorimetry (ITC).…”
Section: Therapeutic Targeting Of the Mll-fusion Protein Epigenetic Nmentioning
confidence: 99%
“…Christott et al (2018) screened a library of 24,000 compounds using a peptide displacement assay and discovered a small molecule (XS018661) that binds to AF9 and ENL with equilibrium dissociation constant ( K d ) values of 523 ± 53 and 745 ± 45 nM, respectively, as determined by isothermal calorimetry (ITC). Li et al (2018), on the other hand, used structure-guided development to produce selective peptide-based AF9 and ENL inhibitors, termed XL-13a and XL-13m, respectively. They also showed that XL-13m down-regulated key leukemic driver genes including MYC , MYB (a transcriptional activator), HOXA9 , and MEIS1 in MOLM-13 cells (Li et al, 2018).…”
Section: Therapeutic Targeting Of the Mll-fusion Protein Epigenetic Nmentioning
confidence: 99%
See 1 more Smart Citation
“…These distinct structural features suggest that YEATS domain inhibitors require different structural features compared to acetyl-lysine mimetic groups explored for the development of bromodomain inhibitors [22][23] . An early attempt exploiting a peptide-based strategy with 2-furancarbonyl lysine led to a competitive nanomolar binder 24 , demonstrating potential inhibitions of the YEATS protein module. Our recent screening efforts alternatively revealed a number of small molecule binders for MLLT1/3 21,25 .…”
mentioning
confidence: 99%